Entrepreneurial Role Networking , Digitalization Of Information And Utilization Of Collaboration For Business Growth in Coffee Shop in Sukabumi City (Survey on Coffeeshop in Sukabumi City) - Machmudin, Arief; R. Deni Muhammad Danial; Nor Norisanti (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of entrepreneurial networking, information digitalization, and collaboration on business growth in coffee shops in Sukabumi City. The phenomenon of the rise and fall of the number of coffee shops in recent years indicates a significant challenge in maintaining and developing businesses in this sector. The research approach used is quantitative with descriptive and associative research types. Primary data were collected through questionnaires from 42 coffee shops which were the population and samples using saturated sampling techniques. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression, F tests and t tests. The results of the study indicate that entrepreneurial networking, information digitalization, and collaboration have a positive and significant influence on business growth. Information digitalization makes the greatest contribution to driving operational efficiency, expanding markets, and increasing customer interaction. Entrepreneurial networking helps business actors build strategic relationships that have an impact on expanding access to information and business resources. Meanwhile, collaboration between business actors has proven effective in increasing innovation, expanding marketing networks, and overcoming internal limitations. The implications of this study indicate that coffee shops in Sukabumi City need to optimize the use of information technology, actively expand business networks, and establish strategic collaborations with various parties to encourage sustainable business growth. This study is expected to be a reference for MSME actors and academics in understanding the factors that influence business growth in the digital era.